Diagnostic performance of aPS/PT antibodies in neuropsychiatric lupus and cardiovascular complications of systemic lupus erythematosus. (2nd January 2020) - Ramirez, Giuseppe A.; Canti, Valentina; Del Rosso, Stefania; Erra, Roberta; Moiola, Lucia; Magnoni, Marco; Bozzolo, Enrica P.; Manfredi, Angelo A.; Rovere-Querini, Patrizia
Abstract: Background: Systemic lupus erythematosus (SLE) is associated with a constellation of complications affecting multiple organs, including neuropsychiatric manifestations (NPSLE) and ischaemic events, leading to increased long-term morbidity. Antiphospholipid antibodies (aPL) are a major determinant of vascular inflammation and thromboembolic risk. The diagnostic role of anti-phosphatidylserine/prothrombin (aPS/PT) antibodies in this setting is incompletely defined. Aim: To verify whether aPS/PT add to diagnostics and disease stratification in patients with SLE with or without other aPL. Methods: 131 consecutive patients were studied, including 20 patients with SLE and secondary antiphospholipid syndrome (APS). aPS/PT IgG and IgM were assessed through ELISA and patients were stratified based on the presence of other aPL, on their clinical and laboratory features at time of blood sampling and on their clinical history. Synthetic indices of disease activity, chronic damage and cardiovascular risk were calculated at time of venipuncture. Results: Fifty-one (38.9%) patients with SLE had aPS/PT and 15 (11.5%) patients had aPS/PT as the only aPL (aPS/PT-only). aPS/PT-only patients had a significantly higher prevalence of NPSLE than quadruple aPL-negative patients ( p  = .007). Patients with aPS/PT were more likely to have a history of ischaemia, thrombocytopenia and Libman–Sacks' endocarditis. The presence of aPS/PT also associated with previous accrual of at least one damage item ( p  = .043), but had limited predictive values for damage progression in the short term. Conclusion: aPS/PT antibodies provide non-redundant information that could contribute to risk assessment and stratification of patients with SLE.